Policy Work and Politicisation in the Ministries of the Czech Republic: The Dilemmas of State Service - Kohoutek, Jan (Karolinum, 2024)
Over the past thirty years, the Czech public administration has been the subject of research rooted in law, economics, and history. However, only minimal attention has been paid to what Czech public officials actually do on the job (policy work) and the extent of politically motivated interference in their work (politicisation). This book aims to fill this gap by presenting the evidence derived from a large-N survey of the Czech ministries, the first of its kind in the country. The findings presented in the book offer new insights into the activities within the "ivory towers" of the Czech ministries and defy popular notions of an appallingly politicised bureaucracy.
Keywords: Politologie